Birds seen and not seen during the COVID-19 pandemic: The impact of lockdown measures on citizen science bird observations. (April 2021) - Basile, Marco; Russo, Luca Francesco; Russo, Valerio Giovanni; Senese, Andrea; Bernardo, Nicola
Abstract: In early 2020, the rapid spread of the novel coronavirus disease 2019 (COVID-19) led multiple countries to introduce strict lockdown measures to contain the pandemic. Movement restrictions may have influenced the ability of the public to contribute to citizen science projects. We investigated how stay-at-home orders affected data submitted by birdwatchers in Italy, Spain and the United Kingdom (UK) to a widely-used citizen science platform, iNaturalist, depending on whether observations were collected in urban or non-urban areas. We found significant trends in the daily number of observations in all three countries, indicating a surge in urban observation during lockdowns. We found an increase in the mean daily number of urban observations during the lockdown in Italy and Spain, compared to previous years. The mean daily number of non-urban observations decreased in Italy and Spain, while remained similar to previous years in the UK. We found a general decrease of new records during the lockdowns both in urban and non-urban areas in all countries. Our results suggest that the citizen science community remained active during the lockdowns and kept reporting birds from home. However, limitations to movements may have hampered the possibility of birdwatchers to explore natural areas and collect new records. Our findings suggest that future research and conservation applications of citizen science data should carefully consider the bias and gaps in data series caused by the pandemic. Furthermore, our study highlights the potential of urban areas for nature activities, such as birdwatching, and its relevance for sustainable urban planning. Graphical abstract: Unlabelled Image Highlights: COVID-19-related lockdowns influenced citizen science projects. Lockdowns increased citizen science observations from urban areas in Italy, Spain and the UK. Non-urban observations decreased in Spain. A decrease in new records is particularly evident in non-urban areas.